Propuesta de mejoramiento de la vía terciaria alterna que conduce del municipio de cáqueza al municipio de ubaque, comenzando en la variante girón de blancos hasta el sector conocido como el alto de la virgen (2022)
This Project consists of implementing a proposal to improve the tertiary road network in the municipality of Cáqueza (Cundinamarca), “ALTERNATIVE TERTIARY ROAD THAT COMMUNICATES THE MUNICIPALITY OF CÁQUEZA WITH THE MUNICIPALITY OF UBAQUE, STARTING AT THE VARIANT OF THE VEREDA GIEÓN DE BLANCOS UNTIL THE SECTOR KNOWN AS EL ALTO DE LA VIRGEN”. Studying the regulations implemented by the National Institute of roads (INVIAS, 2016) and the Ministry of Transport, having as objective the aspects in the execution of existing policies, strategies, plans and programs embodied in the technical manuals for the Maintenance of unpaved roads and verifying the current state of this alternative tertiary road, complying with the requirements for the orientation of an improvement proposal. In this way, to be able to minimize the negative impacts generated by the deterioration of this tertiary road and especially reducing the unfavorable effects against the economy of these municipalities and improving the quality of life of the population